Microcurrent wave alleviates mouse intracranial arterial dolichoectasia development - Jae Hee Lee; Huy Duc Vu; Min Hee Park; Phuong Tu Huynh; Sung Won Youn; Dong Rak Kwon (Scientific Reports, 2024)
Abstract Intracranial arterial dolichoectasia (IADE) is associated with the interaction of hypertension and inflammation, and microcurrent can be effective in hypertension. Therefore, this study aimed to investigate the therapeutic effect of microcurrent electrical stimulation in a mouse IADE model. This study randomly categorized 20 mice into five groups: group 1-C (healthy control), group 2-D (IADE model), group 3-M + D (microcurrent administration before nephrectomy and until brain surgery), group 4-D + M (microcurrent administration for 4 weeks following brain surgery), and group 5-M (microcurrent administration for 4 weeks). Cerebral artery diameter and thickness and cerebral arterial wall extracellular matrix components were assessed. Among the five groups, group 2-D showed significantly higher cerebral arterial wall diameter (117.79 ± 17.05 µm) and proportion of collagen (42.46 ± 14.12%) and significantly lower arterial wall thickness (9.31 ± 2.26 µm) and proportion of smooth muscle cell (SMC) and elastin in the cerebral arterial wall (SMC: 38.05 ± 10.32%, elastin: 11.11 ± 6.97%). Additionally, group 4-D + M exhibited a non-significantly lower diameter (100.28 ± 25.99 µm) and higher thickness (12.82 ± 5.17 µm). Group 5-M demonstrated no evidence of toxicity in the liver and brain. The pilot study revealed that microcurrent is effective in preventing IADE development, although these beneficial effects warrant further investigation.